Faktor-faktor yang Memengaruhi Perilaku Konsumen dalam Bertransaksi di Media Sosial - Irfan Aulia Syaiful; Anggit Verdaningrum Kumala Sari (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2016)
Abstract: This research is in the area of consumer behavior. Many of these factors can be confusing for company to map consumer behavior into its target market. Therefore, the purpose of this study was to determine the factors influencing consumer behavior transactions in social media. This research using qualitative method. Our subjects involved 5 consumers who make transactions in social media. Techniques of data collection is done by observation and structured interviews, while the data collection tool used as interview guides and recorder. Based on the results it was found that four of these factors influence consumer behavior in social media, in the cultural factors such as between consumers and sellers adjust to each other in the language selection, social factors such as testimonials, offer from a friend, how the seller described the product, personal factors such as convenience at shopping (even when in the bathroom), while psychological factors such as discounts, product packaging and delivery speed.Abstrak: Banyak faktor yang membingungkan perusahaan dalam memetakan perilaku konsumen yang menjadi targetnya. Penelitian ini berupaya menggambarkan faktor-faktor yang memengaruhi perilaku transaksi konsumen di media sosial. Metode yang digunakan adalah kualitatif yang melibatkan sebanyak 5 orang dengan karakter telah sering melakukan transaksi belanja lewat media sosial. Teknik pengambilan data dilakukan dengan observasi dan wawancara terstruktur. Hasil penelitian menunjukkan, ada tiga faktor yang memengaruhi perilaku konsumen di media sosial. Pertama, faktor budaya seperti antara kesesuaian bahasa antara konsumen dan penjual, faktor sosial seperti testimonial, tawaran dari teman, cara penjual mendeskripsikan produk. Kedua, faktor pribadi seperti kemudahan berbelanja. Ketiga, faktor psikologis seperti diskon, waktu pengiriman, dan pengemasan produk.